Kaidah fiqih siyasah dalam perubahan hukum. - oganse, fatihurrohman; Daironi, Maiya Hasanatud; Daironi, Maiya Hasanatud; Jinan Al-Gahzy, Rafi Hara; Jinan Al-Gahzy, Rafi Hara; Al Fardi, Muhammad Wirdiyan; Zamroni, Muh; Zamroni, Muh (Maliki Interdisciplinary Journal, 2025)
Legal change in fiqh siyasah reflects Islam’s adaptability to time, place, and societal needs. Guided by legal maxims such as “Taghayyur al-fatwa bitaghayyur al-azman wa al-ahwal” and “La yunkar taghayyur al-ahkam bitaghayyur al-azman wa al-amkinah”, Islamic political jurisprudence allows for changes in rulings without compromising Sharia principles. These changes aim to ensure public benefit and uphold the objectives of Islamic law (maqasid al-sharia). This study emphasizes that legal reform must remain within the boundaries of permissibility and not contradict established prohibitions or obligations. The findings highlight the importance of contextual yet principled Islamic legal thought in governance and lawmaking.